Entre humour noir et réflexivité : écouter la voix de Moss dans No Country for Old Men - Françoise Sammarcelli (Revue LISA)
This essay examines the voice of Llewelyn Moss, a man of action and hunter who becomes a prey. Though it is seldom analysed by critics, this voice evinces intriguing qualities that complexify our perception of the character, between pragmatism, humour and reflexivity. The paper first studies brief monologues in which Moss speaks to himself as if to another and which acquire a dialogic dimension. Then it focuses on a few conversations, in particular the remarkable one with the guard at the border in chapter VI and the long conversation with the young hitchhiker (in chapters VII and VIII). The latter slows down the rhythm by introducing discontinuity in the sequence of dramatic actions and combines wisecracking and philosophical reflections; it is also endowed with a special status as it contains Moss’s last words in the text. Lastly, it is worth observing how the film adapts these theatrical or incongruous moments and what it achieves by reducing Moss’s spoken presence, replacing it by visual reflexivity and an increased dramatic tension.